2019
DOI: 10.2147/jpr.s189390
|View full text |Cite
|
Sign up to set email alerts
|

<p>The low-frequency BOLD signal oscillation response in the insular associated to immediate analgesia of ankle acupuncture in patients with chronic low back pain</p>

Abstract: Purpose The present study evaluated the modulation effect of a painless acupuncture technique, ankle acupuncture (AA), on resting-state functional change in patients with chronic low back pain (CLBP). Patients and methods Fourteen participants diagnosed with CLBP received AA and underwent one brain functional image scan after tactile stimulation and another one following the insertion of the needle. The needling sensations and clinical pain intensities were evaluated af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 45 publications
5
18
0
Order By: Relevance
“…A total of 310 results were yielded from the databases. After deduplication and screening phases, 19 studies (Ji et al, 2007 ; Junhai et al, 2008 ; Yongsong et al, 2011 ; Li et al, 2012 , 2014 ; Guoqiang et al, 2014 ; Jialiang et al, 2014 ; Tao et al, 2015 ; Lin and Xianmo, 2017 ; Yijun et al, 2017 ; Makary et al, 2018 ; Lee et al, 2019 ; Tu et al, 2019 ; Xiang et al, 2019 ; Yan et al, 2019 ; Kim et al, 2020 ; Lan et al, 2020 ; Liu et al, 2020 ; Yu et al, 2020 ) between 2007 and 2020 were incorporated in this review ( Table 1 ). Among the articles, 14 studies were performed in China (Ji et al, 2007 ; Junhai et al, 2008 ; Yongsong et al, 2011 ; Li et al, 2012 , 2014 ; Guoqiang et al, 2014 ; Jialiang et al, 2014 ; Tao et al, 2015 ; Lin and Xianmo, 2017 ; Yijun et al, 2017 ; Xiang et al, 2019 ; Yan et al, 2019 ; Lan et al, 2020 ; Liu et al, 2020 ), three were conducted in the USA (Tu et al, 2019 ; Kim et al, 2020 ; Yu et al, 2020 ), and two were conducted in South Korea (Makary et al, 2018 ; Lee et al, 2019 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A total of 310 results were yielded from the databases. After deduplication and screening phases, 19 studies (Ji et al, 2007 ; Junhai et al, 2008 ; Yongsong et al, 2011 ; Li et al, 2012 , 2014 ; Guoqiang et al, 2014 ; Jialiang et al, 2014 ; Tao et al, 2015 ; Lin and Xianmo, 2017 ; Yijun et al, 2017 ; Makary et al, 2018 ; Lee et al, 2019 ; Tu et al, 2019 ; Xiang et al, 2019 ; Yan et al, 2019 ; Kim et al, 2020 ; Lan et al, 2020 ; Liu et al, 2020 ; Yu et al, 2020 ) between 2007 and 2020 were incorporated in this review ( Table 1 ). Among the articles, 14 studies were performed in China (Ji et al, 2007 ; Junhai et al, 2008 ; Yongsong et al, 2011 ; Li et al, 2012 , 2014 ; Guoqiang et al, 2014 ; Jialiang et al, 2014 ; Tao et al, 2015 ; Lin and Xianmo, 2017 ; Yijun et al, 2017 ; Xiang et al, 2019 ; Yan et al, 2019 ; Lan et al, 2020 ; Liu et al, 2020 ), three were conducted in the USA (Tu et al, 2019 ; Kim et al, 2020 ; Yu et al, 2020 ), and two were conducted in South Korea (Makary et al, 2018 ; Lee et al, 2019 ).…”
Section: Resultsmentioning
confidence: 99%
“…After deduplication and screening phases, 19 studies (Ji et al, 2007 ; Junhai et al, 2008 ; Yongsong et al, 2011 ; Li et al, 2012 , 2014 ; Guoqiang et al, 2014 ; Jialiang et al, 2014 ; Tao et al, 2015 ; Lin and Xianmo, 2017 ; Yijun et al, 2017 ; Makary et al, 2018 ; Lee et al, 2019 ; Tu et al, 2019 ; Xiang et al, 2019 ; Yan et al, 2019 ; Kim et al, 2020 ; Lan et al, 2020 ; Liu et al, 2020 ; Yu et al, 2020 ) between 2007 and 2020 were incorporated in this review ( Table 1 ). Among the articles, 14 studies were performed in China (Ji et al, 2007 ; Junhai et al, 2008 ; Yongsong et al, 2011 ; Li et al, 2012 , 2014 ; Guoqiang et al, 2014 ; Jialiang et al, 2014 ; Tao et al, 2015 ; Lin and Xianmo, 2017 ; Yijun et al, 2017 ; Xiang et al, 2019 ; Yan et al, 2019 ; Lan et al, 2020 ; Liu et al, 2020 ), three were conducted in the USA (Tu et al, 2019 ; Kim et al, 2020 ; Yu et al, 2020 ), and two were conducted in South Korea (Makary et al, 2018 ; Lee et al, 2019 ). Five kinds of diseases were involved in these studies: chronic low back pain (Li et al, 2014 ; Tu et al, 2019 ; Xiang et al, 2019 ; Yan et al, 2019 ; Kim et al, 2020 ; Yu et al, 2020 ), non-specific low back pain (Makary et al, 2018 ; Lee et al, 2019 ), lumbar disc herniation (Yongsong et al, 2011 ; Guoqiang et al, 2014 ; Jialiang et al, 2014 ; Tao et al, 2015 ; Lin and Xianmo, 2017 ; Yijun et al, 2017 ; Lan et al, ...…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, limbic system dysfunction plays an important role in the occurrence, development, and regulation of migraines. Further study of acupuncture analgesia [ 49 ] found that the amplitude of low-frequency fluctuation (ALFF) in left insula decreased in patients with chronic low back pain after acupuncture, and the decrease of average ALFF was positively related to the decrease of VAS value, which confirms that regulating the function of limbic system may be one of the mechanisms for endogenous analgesia. The taVNS could regulate amygdala activity from a recent study [ 50 ] and caused extensive negative activation in the limbic system [ 30 ].…”
Section: Discussionmentioning
confidence: 98%
“…Interestingly, wrist-ankle acupuncture, a needling method via inserting the needle through the skin shallowly in the subcutaneous tissue level in the wrist or ankle without manipulation and needle sensation, exerts similar analgesic effect to traditional acupuncture [52]. Xiang et al found that this shallow and no sensory inputting needling method induced the low-frequency BOLD signal oscillation response in the left insular in patients with chronic low back pain [53]. Concerning the results of the current study, it seems that analgesic effects achieved by invasive needling at an acupoint without deqi may be correlated with some kinds of activities among some structures in the brain.…”
Section: Discussionmentioning
confidence: 99%